Distributed multicell beamforming scheme with limited intercell communication - Yong-ming HUANG; Ying-gang DU; Hui YU; Lv-xi YANG (Tongxin xuebao)
Coordinated downlink beamforming optimization was studied for the time division duplexed(TDD)multicell system with limited inter-BS communication.With the objective to reach the particular point on the Pareto boundary of user rates with the maximum worst-user rate,a near-optimal two-step centralized solution was first proposed.Based on that,a distributed solution was then developed,in which only limited number of positive scalars were needed to exchange between the BSs.Numerical simulation results show that the proposed distributed solution achieves a rate performance close to the centralized solution.